PENGARUH KONFLIK PERAN TERHADAP ORGANIZATIONAL CITIZHESHIP BEHAVIOR PEGAWAI - Darwin Sirait; Bunga Rosario Hutabarat; Dumai Yanti Hutauruk; Julia Inda Sari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
The role of human resources in an organization is very influential in increasing its main objectives. So it is important to pay attention to human resources. This study intends to reveal the effect of role conflict on organizational citizenship behavior of employees. Collecting data in this study using quantitative methods with an initial survey with a sample of 48 people. This study reveals that the significant influence of Role Conflict on the Organizational Citizenship Behavior of employees at the Tanjung Balai Branch Health Insurance Administration Agency (BPJS) is 2,035 on the Organizational Citizenship Behavior of employees of the Health Insurance Provider (BPJS) Tanjung Balai Branch.